New earthworm species of the genus Amynthas from Hainan Island, China (Megascolecidae, Clitellata) - Zhao, Qi; Yao, Xuanzhu; Lan, Yaqiong; Xu, Junxian; Qiu, Jiangping (Zootaxa, 2018)
Three new species of earthworms belonging to the genus Amynthas are described from Hainan Island, China. They are named Amynthas wenchangensis sp. nov., Amynthas accessorius sp. nov., and Amynthas eumorphus sp. nov. A. wenchangensis sp. nov. keys to the Amynthas morrisi-group; it has several small genital papillae in the male pore region and a degenerated prostate. A. accessorius sp. nov. keys to the Amynthas hawayanus-group and has completely degenerated prostates and two large accessory glands. A. eumorphus sp. nov. keys to the Amynthas sieboldi-group.